O levante dos "invisíveis" da história : o movimento indígena no Equador na década de 1990 - Sousa, Adilson Amorim de (2006)
Through the last decades, among the several manifestations of social movements occurred in various countries of Latin America, we have to stand out the movements that took place in the rural areas, specially those ones that were conducted by indian organizations. These types of manifestations have played an important role in the search for another pattern of social and political organization based in respect to different kinds of patterns and cultural values. This paper objectifies specifically to understand the new features revealed by the indian movement in Ecuador, in the 90’s, since its several organizations were unified during the Conaie – Confederación de Nacionalidades Indígenas del Ecuador. Nowadays this entity is the most expressive in the popular endurance concerning the economic and political pattern settled by the State through the dispersion of neoliberal doctrines. The objective is, therefore, to indentify the guide matrices of this organization, as well as its various mobilization forms and acting stratagies. The discussion is also about the political practices in the indian movement, its insertion in the social sectors, its connections with the State and its proposals on the political and economic organization to the country. This research allows to characterize the Conaie from its ideological expression and acting strategy, showing it as the keeper of the fusion of ethnic and cultural ideas with popular factors. This point of view has allowed the indian movement to establish connections with other sectors and to share with them ordinary problems, making possible its entrance as the main social and political agent of the country.